ANALISIS SAMBUNGAN BALOK PRECAST SEDERHANA DENGAN SISTIM DOUBLE LAPSPLICES MIDDLE WET JOINT DI MOMEN MAKSIMUM - Andrias Rudi Hermawan; EKA SM (Jurnal Poli-Teknologi, 2013)
ABSTRACT This research about connection of precast simple beam with double lapsplices middle wet joint system have finished with comparing of flexure strength between precast beam with connection at meddle span (middle wet joint) and conventional beam. Performance of flexure strength of precast beam with connection at meddle span (middle wet joint) is better than conventioanal beam, can be proved to curve of deflection – load between conventional beam (1 and 2) with precast beam with connection at meddle span (middle wet joint 1 and 2). Base on that curve, can be known that precast beam with connection at meddle span (middle wet joint 1) have deflection10 mm at 151,8 kn and precast beam with connection at meddle span (middle wet joint 2) have deflection16 mm at 169,2 kn and conventional beam 1 have deflection 47 mm at 145,5 kn and conventional beam 2 have deflection 40 mm at 144,7 kn Keynote : prestressed,precast,boned nonprestressed,concrete